2020
DOI: 10.48550/arxiv.2006.01857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blazars at the Cosmic Dawn

Vaidehi S. Paliya,
M. Ajello,
H. -M. Cao
et al.

Abstract: The uncharted territory of the high-redshift (z 3) Universe holds the key to understand the evolution of quasars. In an attempt to identify the most extreme members of the quasar population, i.e., blazars, we have carried out a multi-wavelength study of a large sample of radio-loud quasars beyond z = 3. Our sample consists of 9 γ-ray detected blazars and 133 candidate blazars selected based on the flatness of their soft X-ray spectra (0.3−10 keV photon index ≤ 1.75), including 15 with NuSTAR observations. The … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…Note that the parameters in Table 2 are not very extreme. But given that B and δ for other highz (z=3-4) blazars are inferred to be modest (B=1-2 G and δ =10-16; Paliya et al 2020), the low-δ (e.g., <20) models may be preferred for J0131.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the parameters in Table 2 are not very extreme. But given that B and δ for other highz (z=3-4) blazars are inferred to be modest (B=1-2 G and δ =10-16; Paliya et al 2020), the low-δ (e.g., <20) models may be preferred for J0131.…”
Section: Discussionmentioning
confidence: 99%
“…The assumed distributions do not have physical motivations, and they are rather empirically inspired; however we hope that they can provide at least a semi-quantitative estimate of the detectability. First, the combination of the Ghisellini et al ( , 2011; Ghisellini (2013); Ghisellini et al (2015); Paliya et al (2017Paliya et al ( , 2019Paliya et al ( , 2020 observed samples shows that the log 𝐵, Γ and log 𝑟 blob follow distributions similar to Gaussian shape, with log 𝐵 = 0.2, 𝜎 log 𝐵 = 0.2, Γ = 11, 𝜎 Γ = 2.5, and log 𝑟 blob = 1.9, 𝜎 log 𝑟 blob = 0.3. Since there is no any prior knowledges about jets of DCBHs, we borrow these statistics directly.…”
Section: Signal Detectabilitymentioning
confidence: 95%
“…𝑟 blob ∼ 50 𝑟 𝑆 , 𝐵 ∼ 1 G, Γ ∼ 10, 𝛾 break ∼ 70 − 300, 𝛾 max ∼ 3000, and 𝑃 r /𝑃 jet ∼ 0.02 − 0.13. Paliya et al (2017Paliya et al ( , 2019Paliya et al ( , 2020 analyzed a sample of blazars and found 𝑟 blob ∼ 50 − 200 𝑟 𝑆 , 𝐵 ∼ 1 G, Γ ∼ 10, the spectrum index of the electrons distribution below 𝛾 break is ∼ 2 where 𝛾 break ∼ 100, and 𝑃 r /𝑃 jet ∼ 0.02 − 0.13. Motivated by the above observations, we adopt some jet parameter sets for the following investigation, see the jet 1, 2 and 3 listed in Tab.…”
Section: Jet Radiation Spectrummentioning
confidence: 99%